A model for mitotic inheritance of histone lysine methylation - Xu, Mo (Nature Publishing Group, 2012)
Histone lysine methylation has been implicated in epigenetic regulation of transcription. Using stable-isotope labelling and quantitative mass spectrometry, we analysed the dynamics of histone lysine methylation. Here we report that histone methylation levels are transiently reduced during S phase and are gradually re-established during subsequent cell cycle stages. However, despite the recovery of overall methylation levels before the next S phase, the methylation levels of parental and newly incorporated histones differ significantly. In addition, histone methylation levels are maintained at steady states by both restriction of methyltransferase activity and the active turnover of methyl groups in cells undergoing an extended G1/S phase arrest. Finally, we propose a ‘buffer model' that unifies the imprecise inheritance of histone methylation and the faithful maintenance of underlying gene silencing.